Varying Dose of Atropine in Slowing Myopia Progression in Children Over Different Follow-Up Periods by Meta-Analysis - Gan, Jiahe; Li, Shi-Ming; Wu, Shanshan; Cao, Kai; Ma, Dandan; He, Xi; Hua, Ziyu; Kang, Meng-Tian; Wei, Shifei; Bai, Weiling; Wang, Ningli (Frontiers in Medicine, 2022)
Purpose: To evaluate the efficacy and safety of atropine for slowing myopia progression and to investigate whether the treatment effect remains constant with continuing treatment. Method: Studies were retrieved from MEDLINE, EMBASE, and the Cochrane Library from their inception to May 2021, and the language was limited to English. Randomized controlled trials (RCTs) and cohort studies involving atropine in at least one intervention and placebo/non-atropine treatment in another as the control were included and subgroup analysis based on low dose (0.01%), moderate dose (0.01%–<0.5%), and high dose (0.5–1.0%) were conducted. The Cochrane Collaboration and Newcastle-Ottawa Scale were used to evaluate the quality of RCTs and cohort studies, respectively. Results: Twelve RCTs and fifteen cohort studies involving 5,069 children aged 5 to 15 years were included. The weighted mean differences in myopia progression between the atropine and control groups were 0.73 diopters (D), 0.67 D, and 0.35 D per year for high-dose, moderate-dose, and low-dose atropine, respectively (χ2 = 13.76; P = 0.001, I2 = 85.5%). After removing studies that provided extreme findings, atropine demonstrated a significant dose-dependent effect on both refractive change and axial elongation, with higher dosages of atropine resulting in less myopia progression (r = 0.85; P = 0.004) and less axial elongation (r = −0.94; P = 0.005). Low-dose atropine showed less myopia progression (−0.23 D; P = 0.005) and less axial elongation (0.09 mm, P < 0.001) in the second year than in the first year, whereas in high-dose atropine more axial elongation (−0.15 mm, P = 0.003) was observed. The higher dose of atropine was associated with a higher incidence of adverse effects, such as photophobia with an odds ratio (OR) of 163.57, compared with an OR of 6.04 for low-dose atropine and 8.63 for moderate-dose atropine (P = 0.03). Conclusion: Both the efficacy and adverse effects of atropine are dose-dependent in slowing myopia progression in children. The efficacy of high-dose atropine was reduced after the first year of treatment, whereas low-dose atropine had better efficacy in a longer follow-up period.